Pengaruh Reward, Sarana Dan Prasarana, Dan Coaching Performance Satisfaction Di Pusat Pelatihan Olahraga Pelajar Dki Jakarta Melalui Motivasi Sebagai Intervening - Dlis, Rizky Fazri; Handaru, Agung Wahyu; Suhud , Usep (Politeknik Siber Cerdika Internasional, 2023)
The sustainable sports training program is the government's effort to create quality athletes through a training approach from an early age. This program is divided into three stages, namely the Sustainable Achievement Sports Development (POPB) aimed at athletes under the age of 15, the Student Sports Training Center (PPOP) for junior and senior high school students, and the Student Training Development Center (PPLM). The aim of this program is to group athletes based on age, select potential athletes, and develop their abilities from an early age. In order for athletes in PPOP to achieve their best performance, it is necessary to regulate the management of available resources and ensure that their motivation continues to grow. In this context, athletes are considered as human capital that needs to be empowered. This approach is in accordance with the concept of human resource management, where humans are considered as the most important assets in achieving organizational goals (Aslam et al., 2014). This study used a quantitative method involving 201 respondents. Analysis was performed using the Structural Equation Model (SEM). The results of this study reveal several things: This study used a quantitative method with a total of 201 respondents. With the analytical tool used, namely using the Structural Equation Model (SEM). The results of this study are in the reward hypothesis has a positive relationship to motivation found that reward has a significant positive relationship to motivation. In the hypothesis that facilities and infrastructure have a positive relationship to motivation, it is found that facilities and infrastructure do not have a positive relationship to motivation. In the hypothesis that coaching has a positive relationship to motivation, it is found that coaching has a significant positive relationship to motivation. In the hypothesis that there is a positive influence between motivation on Performance Satisfaction. It is found that motivation has a significant positive relationship with performance satisfaction. In the reward hypothesis, it is found that reward has a positive relationship with performance satisfaction.